Academic assistance centers: focusing on psychosocial variables of academic success for multicultural and academic probation students. - Morgan, Troy P. (Kansas State University, 2011)
Student affairs personnel in higher education have an extraordinary ability to affect positively the academic, personal, social, emotional, and vocational development of students, as well as to provide an understanding of the challenges that students experience. In addition, an increase in investigating student success, as well as how to quantify success has occurred. The purpose of this report is to reflect the areas of student development upon which student affairs personnel can have a profound impact—that being the psychosocial variables to student success. In combination with exploring how Academic Assistance Centers (AAC’s) focus on psychosocial factors that influence student success, this report looks at the similarities between theory and the pragmatic programming that one particular Midwestern university employs to help facilitate student awareness and practice of psychosocial factors. The overarching belief of the author is that students can and will find success through challenge and support. This report will demonstrate, through a brief history of the challenges that higher education has faced, how student affairs personnel are often times the first and last line of defense in student support. Moreover, student affairs personnel have been charged with the task of providing support to an ever growing diverse student body in addition to providing the proper support needed to enhance the academic and personal success of such a diverse student body. Through a review of the literature investigating student attrition as well as retention, two subgroups of undergraduates were specifically identified as to how academic assistance centers can facilitate their success and, ultimately, their retention. The two subgroups are students who identify as multicultural and students who are on academic probation. Lastly, the author offers suggestions on what student affairs personnel, as well as higher education, can do to facilitate holistic student development and promote the awareness of psychosocial variables that will aid students in their academic development and success.
Keywords: Psychosocial; Multicultural; Academic probation; Academic Success; College Students; Adult Education (0516); Counseling Psychology (0603); Educational Psychology (0525)